1993
DOI: 10.1023/a:1018913628568
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The dissolution and bioavailability of etodolac from capsules exposed to high relative humidity and temperature were compared to those from capsules stored at room temperature (RT). Dissolution of stressed and control capsules was evaluated using a USP basket apparatus at 100 rpm with 900 mL pH 7.5 phosphate buffer (0.05 M) at 37 degrees C. The dissolution of etodolac from capsules exposed to stressed conditions was also evaluated with enzymes (pancreatin, 1%, w/v) added to the dissolution medium. The bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Dey et al, [12] have reported the dissolution and bioavailability of etodolac from capsules exposed to high relative humidity and temperature that were compared to those from capsules and evaluated using a USP basket apparatus at 100 rpm with 900 ml pH 7.5 phosphate buffer (0.05 M) at 37°C as mentioned in United States Pharmacopeia.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dey et al, [12] have reported the dissolution and bioavailability of etodolac from capsules exposed to high relative humidity and temperature that were compared to those from capsules and evaluated using a USP basket apparatus at 100 rpm with 900 ml pH 7.5 phosphate buffer (0.05 M) at 37°C as mentioned in United States Pharmacopeia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The combination tablets were being developed in three dosage strengths, 800/20, 800/40 and 800/80 mg of ET/PH [7] . Analytical methods reported in United States Pharmacopeia, British Pharmacopeia and other published literatures [8][9][10][11][12][13][14] , mainly state about the dissolution method for the individual dosage form of PH and ET. Several LC and LC-MS methods were published for the determination of both ET and PH individually, or in combination with other drug substances.…”
Section: Scope Of the Studymentioning
confidence: 99%